Tactics, Strategy, and Marriage Equality - Rosen, Hilary (Columbia Journal of Gender and Law, 2015)
Thank you for having me. I’m going to focus my remarks today on being tactical. As law students, hopefully you will all go into the social justice field and go on and do great things for everyone, but frankly a lot of what I’m going to talk about in these couple of minutes will be as relevant for almost any set of litigation or legal problems that you have, almost any kind of high-profile cases.